Exploring the effect of augmented reality technology on high school students’ vocabulary learning, personality traits, and self-efficacy in flipped and blended classes - Khodabandeh, Farzaneh; Mombini, Azimeh (Education and information technologies, 2024)
Incorporating augmented reality (AR) technology into education has the incredible capacity to elevate the quality of learning encounters significantly. In flipped and blended classrooms, where technology complements traditional instruction, investigating the effect of AR on vocabulary learning, self-efficacy, and personality traits becomes crucial due to the immense potential AR holds for enhancing learning experiences.This study explores the effects of AR on EFL high school students’ vocabulary learning, personality traits, and self-efficacy in flipped and blended classes. The study involved the selection of participants according to their scores on the Oxford Young Learners Placement Test at the Elementary level. These individuals were then randomly divided into two experimental groups and one control group. Pre-tests assessed initial vocabulary abilities, while self-efficacy and personality traits questionnaires measured students’ perceptions. AR-based instruction was implemented in flipped and blended classes, with all groups receiving vocabulary instruction over 12 sessions. Participants independently used a Vocabulary Builder AR app on their cell phones for AR-based instruction. Post-tests and the same self-efficacy and personality traits questionnaires were administered after the treatment to assess changes in perceptions. The findings revealed that the experimental groups demonstrated superior performance compared to the control group in terms of vocabulary learning, self-efficacy, and personality traits. The research showcases the beneficial effects of implementing AR on students’ vocabulary learning, self-efficacy, and personality traits.The findings hold implications for the development of innovative instructional approaches, curriculum design, and the integration of technology in language education.